BIOMARKERS: AN IMPERATIVE ACCESSION FOR DIAGNOSIS OF A DISEASE AND DRUG DEVELOPMENT - Gulshan, Mohammad; Rao, Nadendla Rama (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Biomarkers are becoming an essential part of clinical development, not least because they offer a faster alternative to the conventional drug development approach and the promise of safer drugs, in greater numbers, approved more quickly. Many of the failures happen late in clinical trials, with the consequence that expenditure in clinical drug development â€“ already a mammoth effort requiring a huge amount of money, time, and patient is increasing. The ultimate vision is to have access to therapeutic fields, a better understanding of pathophysiology of diseases, thereby uncovering potential drug targets and biomarkers in the disease pathway. By finding molecular biomarkers of the disease, diagnosis could be improved and could reveal new information about the disease, by which a better chance for developing drugs is possible. Biomarkers can also reflect the entire spectrum of disease from the earliest manifestations to the terminal stages. In this present review, biomarkers of various diseases were enlisted to highlight the overabundance of information necessary for clinicians and scientists to have a thorough understanding of biomarkers and its ability to improve treatment and reduce health-care costs which are potentially greater than in any other area of medical research. Â 